Intelligent Systems will lead to Cost Saving in Gastronomy Tourism (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Gastronomy tourism is one of the significant and fast-growing sectors if one can nurture to meet food desires of tourists/visitors in the hospitality industry. When it comes to hospitality and tourism, United Arab Emirates (UAE) is one of the most influential countries in the world to attract visitors from all over the world. The country is known for popular sightseeing attractions and various fabulous man-made monuments, but there is very less literature available on Gastronomy tourism. What extent local cuisine of UAE is a noteworthy attraction to the UAE tourists?  What is the potentiality of Gastronomy tourism in UAE to attract visitors? How can implementation of intelligent systems will lead to cost saving in Gastronomy tourism? The current study explores and finds the answers to these questions using empirical data collected from 362 respondents in UAE. With the help of SPSS, this study analysed frequency, correlation and Analysis of Variance (ANOVA) on the responses. Culinary community is one of the neglected sectors in the development of tourism sector in the world. The results of this study can gauge the significance of culinary community to the next level. The results of this study found that there is a positive correlation between implementation of intelligent systems and saving cost in gastronomy tourism. The results of ANOVA prove that there is a positive impact that implementation of intelligent systems in various segments of Gastronomy tourism will lead to cost saving and in turn can attract more tourists.